2020
DOI: 10.3390/ijerph17197149
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of and Risk Factors for COVID-19 Infection among Health Care Workers: A Multi-Centre Comparative Study

Abstract: Healthcare workers (HCWs) worldwide are putting themselves at high risks of coronavirus disease 2019 (COVID-19) by treating a large number of patients while lacking protective equipment. We aim to provide a scientific basis for preventing and controlling the COVID-19 infection among HCWs. We used data on COVID-19 cases in the city of Wuhan to compare epidemiological characteristics between HCWs and non-HCWs and explored the risk factors for infection and deterioration among HCWs based on hospital settings. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
1
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 21 publications
2
43
1
3
Order By: Relevance
“…In other words, the infection rates were significantly higher among healthcare workers compared to non-healthcare workers, which was similar to a study in China, which showed that the infection rates were 2.10% and 0.43% among healthcare and non-healthcare workers, respectively [ 30 ]. The results also corroborate findings from previous studies, which discovered that the infection risk of healthcare workers was significantly higher than that of non-healthcare workers [ 8 , 22 , 30 ]. The positive association between being a healthcare worker and COVID-19 status may be explained by several factors experienced particularly by healthcare workers, such as performing certain medical procedures, prolonged contact with infected patients, and working pressures during the pandemic period [ 14 , 16 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In other words, the infection rates were significantly higher among healthcare workers compared to non-healthcare workers, which was similar to a study in China, which showed that the infection rates were 2.10% and 0.43% among healthcare and non-healthcare workers, respectively [ 30 ]. The results also corroborate findings from previous studies, which discovered that the infection risk of healthcare workers was significantly higher than that of non-healthcare workers [ 8 , 22 , 30 ]. The positive association between being a healthcare worker and COVID-19 status may be explained by several factors experienced particularly by healthcare workers, such as performing certain medical procedures, prolonged contact with infected patients, and working pressures during the pandemic period [ 14 , 16 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, most of these studies were conducted in high-income countries [ 8 , 9 , 17 , 18 , 19 ]. Studies examining the determinants of COVID-19 infections among healthcare workers in low- and middle-income countries (LMICs) were only conducted in China [ 16 , 20 , 21 , 22 ]. Thus, our study aims to fill the gap by examining demographic and behavioral correlates of COVID-19 infections among hospital workers in Indonesia, an upper-middle-income country.…”
Section: Introductionmentioning
confidence: 99%
“… 5 A population-based study carried out in Wuhan, China established that HCWs were at increased risk of contracting COVID-19 and that the risk within HCWs differed by job duties. 6 It has been estimated that HCWs experience more than three-fold increased odds of COVID-19 infection. 7 These studies do not directly assess whether or not hospital-specific passive surveillance based on symptomatic case reporting among HCWs reasonably reflects community-wide trends and thus can inform management, for example, for surge planning.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic is considered an unprecedented physical and mental challenge for healthcare workers (HCWs) around the world ( Salazar de Pablo et al, 2020 , Shaukat et al, 2020 ). HCWs being at the frontline of treating patients with confirmed COVID-19 are at higher risk of exposure than the general population ( Ali et al, 2020 , Nguyen et al, 2020 , Wei et al, 2020 , Zheng et al, 2020 ). However, being more healthy they are expected to have better outcome in terms of hospitalization and mortality compared with non-HCWs ( Misra-Hebert et al, 2020 , Wei et al, 2020 , Zheng et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%